Experimental design of 1-dodecanol@methylated melamine-formaldehyde microencapsulated composite phase change material and the application in energy storage field. (1st November 2022) - Xu, Dengji; Shen, Wanyu; Sun, Shiqi; Chen, Yanjun; Lu, Zhumao; Meng, Xiaokai; Wang, Chao; Guo, Li; Liu, Changcheng; Huang, Que
Abstract: The purpose of this study is to explore a new clean and environment protecting composite microcapsule material with 1-dodecanol (DD) as the core and modified methylated melamine-formaldehyde (MMF) as the shell, to meet the needs of low temperature heat or energy storage (0–40 °C). The microencapsulated phase change material (MPCM) base with a mass ratio of 14:3 was synthesized by in-situ emulsion polymerization, then two kinds of additives 10 wt% boron nitride (BN) and 5 wt% BN mixed with 5 wt% carbon nanotubes (CNTs) were applied to solve the defects of easy leakage and low thermal conductivity, while the samples were defined and shorted as BPCM and BCPCM, respectively. The experimental results showed that the prepared BCPCM presented good storage stability in the temperature range of 0–40 °C, which was due to its good thermal conductivity of 0.584 W/m·K, latent heat of 163.8 J/g, and strong supramolecular interaction between 1-DD and MMF. Through charging and discharging tests for batteries under low temperature, BCPCM indicated excellent thermal management performance, which proposed its application potential in the cryogenic storage environments and battery thermal management system (BTMS) field. Graphical abstract: Unlabelled Image Highlights: A series of novel high performance and non-toxic microencapsulated composite phase change materials (CPCMs) were synthesized with 1-dodecanol core and methylated melamine-formaldehyde (MMF) shell. With the addition of boron nitride (BN) and carbon nanotube (CNT) fillers, the prepared BCPCM (CPCM with 5 wt% BN plus 5 wt% CNTs) presented good nucleation and thermal stability. Reasonable analysis and interpretation of asymmetrical endothermal and exothermal curves were provided. The thermal conductivity and latent heat of BCPCM were 0.584 W/m·K and 163.8 J/g, respectively. The leakage rate at 40°C of developed BCPCM was only 3.6%.